2004
DOI: 10.1002/chin.200428150
|View full text |Cite
|
Sign up to set email alerts
|

cis/trans‐Isochromanones. DMAP Induced Cycloaddition of Homophthalic Anhydride and Aldehydes.

Abstract: Benzopyran derivatives R 0350cis/trans-Isochromanones. DMAP Induced Cycloaddition of Homophthalic Anhydride and Aldehydes. -The title reaction affords trans-acids (III) as major products in a highly stereoselective manner. If the reaction of anhydride (I) with aldehyde (IIe) is performed in pyridine, unsaturated anhydride (VIII) is formed. Isolation of this product leaves an acidic residue which gives with diazomethane compounds (X) and (XI) and unexpected fused product (XII). -(BOGDANOV, M. G.; PALAMAREVA*, M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…Scheme 2) consisting of five sequential steps, including demethylation, lactone ring opening, elimination, isomerization, lactone ring closure and decarboxylation reactions. The main part of this mechanism was deduced on the base of our previous experiments (for details see [10]) and the starting diastereomeric mixture of cis-and trans-3-(2,3-dimethoxyphenyl)-6,7-dimethoxy-1-oxoisochroman-4-carboxylic acids (1) was obtained in 10 min from 6,7-dimetoxihomophthalic anhydride and 2,3-dimethoxybenzaldehyde in presence of DMAP/CH2Cl2 [8][9][10][11]. It has to be also mentioned that the target coumarin 3 was isolated in a high purity (>99%) and yield (92%) just by filtration at the end of the reaction, the latter suggesting the proposed reaction credible for the synthesis of a series of polyhydroxylated coumarin derivatives from readily available starting materials at a low cost.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Scheme 2) consisting of five sequential steps, including demethylation, lactone ring opening, elimination, isomerization, lactone ring closure and decarboxylation reactions. The main part of this mechanism was deduced on the base of our previous experiments (for details see [10]) and the starting diastereomeric mixture of cis-and trans-3-(2,3-dimethoxyphenyl)-6,7-dimethoxy-1-oxoisochroman-4-carboxylic acids (1) was obtained in 10 min from 6,7-dimetoxihomophthalic anhydride and 2,3-dimethoxybenzaldehyde in presence of DMAP/CH2Cl2 [8][9][10][11]. It has to be also mentioned that the target coumarin 3 was isolated in a high purity (>99%) and yield (92%) just by filtration at the end of the reaction, the latter suggesting the proposed reaction credible for the synthesis of a series of polyhydroxylated coumarin derivatives from readily available starting materials at a low cost.…”
Section: Resultsmentioning
confidence: 97%
“…In a recent our articles, we demonstrated that polyhydroxylated cis-restricted stilbenes [8,9] or 3-arylcoumarins (2) bearing carboxylic function in their structure [10] can be obtained via one-pot procedure from diastereomeric mixture of methoxylated cis-and trans-3-aryl-3,4-dihydroisocoumarin-4-carboxylic acids [11] by treatment with BBr3. However, just recently we observed that replacement of BBr3 with HBr as a demethylating agent leads to a subsequent reaction, which produces decarboxylated 3-arylcoumarin derivative-the title compound 3 (Scheme 1).…”
Section: Resultsmentioning
confidence: 99%
“…Methyl esters 1 -4 were prepared from the parent acids [11] and diazomethane. Compounds 5-12 were synthesized by a multi-step transformation [12,13] of the carboxylic group in the parent acids obtained from homophthalic anhydride and an aldehyde [11] or ketone. The structures of all compounds and configuration of compounds 1 -8 (see Table 3) were elucidated by 1 H-NMR spectra and X-ray analysis.…”
Section: Theory and Experimentalmentioning
confidence: 99%
“…This is probably due to the electronegative nitro group that facilitates the hydrolysis of these esters. Along with other products, the parent acids were detected by authentic samples [11] in TLC with hexane-ethyl acetate-formic acid (1 : 1 : 0.02). In the case of esters cis-1 and trans-2 without such a substituent the decomposition was partial, making possible the determination of their R F values.…”
Section: Tlc With the Automatically Selected Mobile Phases: Retentionmentioning
confidence: 99%